The Effect of High Doses of Vitamin D Replacement on Hospital Stay Length and Mobilization in Elderly Hip Fracture Patients - Birsel, Olgar; Ünlü, Mehmet Can (Cerrahpaşa Medical Journal, 2024)
Objective: The widespread distribution of the vitamin D receptor across various tissues has expanded the understanding of vitamin D beyond its traditional role in calcium and bone metabolism. Severe vitamin D deficiency not only affects bone health but also impacts various aspects of the musculoskeletal system. This study aims to investigate the immediate postoperative benefits of high-dose vitamin D administration for hip fracture patients. Methods: This study enrolled 85 consecutive patients aged over 60 years with hip fractures at our university hospital between 2013 and 2014. Patients were divided into 2 groups based on fracture location: pertrochanteric fractures in the osteosynthesis group and femoral neck fractures in the arthroplasty group. Each group was further divided based on preoperative vitamin D administration. Perioperative surgical parameters, length of hospital stay, early postoperative physical performance, and occurrence of delirium were recorded. Results: The study included 85 participants undergoing bipolar hemiarthroplasty (n = 34) and proximal femoral nail (n = 51) procedures. No significant differences were observed in delirium incidence, operation duration, bleeding, or perioperative blood pressure between groups. Hemiarthroplasty patients receiving vitamin D showed improved 8-foot up and go test performance, while the proximal femoral nail group had shorter hospital stays. Delirium correlated with age and polypharmacy; however, the incidence of delirium was not influenced by vitamin D supplementation. Conclusion: High-dose vitamin D supplementation significantly reduced hospital stays for osteoporotic proximal femur fractures treated with osteosynthesis using a proximal femoral nail. Vitamin D replacement also improved short-term physical performance in patients with femoral neck fractures treated with hemiarthroplasty. Vitamin D supplementation offers a safe and cost-effective adjunct therapy for the recovery of elderly patients from hip fractures. Cite this article as: Birsel O, Ünlü MC. The effect of high doses of vitamin D replacement on hospital stay length and mobilization in elderly hip fracture patients. Cerrahpaşa Med J. 2024;48(3):289-293.